Development Finite State Machine Agent in Edugame "Hangug Word" Learning Media of Korea Hangul Letters - Nursobah Nursobah; Reza Andrea; Bambang Kurniawan (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2021)
Development the edugame "Hangug Word", learning media of to Korean Hangul letters with game Agent Finite State Machine based on Android. The application used in making the game is Swish max4. In this game, a game agent character is given. In the game agent using the Finite State Machine (FSM) method, the Game Agent will notify the players if they answer incorrectly or correctly in the game. The Finite State Machine method of designing a control system that describes the working principle of the system using three things: state, event, action used in the game agent can provide action and reaction to players when the game is played. The results of making this edugame are .Apk and .Swf which can be run on an Android smartphone.